Buzz Group methodology to improve the english pronunciation skills for A1 students - Vallejo Delgado, Alberto Esteban (2022)
This study presents a methodological proposal based on cooperative learning, with the use of the Buzz Group strategy, which motivates students to develop oral expression skills in small groups. The general objective of the work was to determine the incidence of the Buzz Group strategy to achieve a clear pronunciation in English from a high school student group during the 2021 school year. A qualitative approach at a descriptive and exploratory level was applied. Pre and post-intervention tests were designed from which the main data related to pronunciation and the use of the Buzz Group strategy were obtained. Where the impact of this strategy on English pronunciation was observed, bridging the gap between strategic learning and pronunciation in the communicative language teaching approach. The study recommends paying greater attention to pronunciation and the use of active and cooperative strategies which comprehensively improve the learning of a foreign language.